Risk factors for recurrent venous thromboembolism after unprovoked pulmonary embolism: the PADIS-PE randomised trial. Issue 1 (4th January 2018) - Tromeur, Cécile; Sanchez, Olivier; Presles, Emilie; Pernod, Gilles; Bertoletti, Laurent; Jego, Patrick; Duhamel, Elisabeth; Provost, Karine; Parent, Florence; Robin, Philippe; Deloire, Lucile; Leven, Florent; et al.
We aimed to identify risk factors for recurrent venous thromboembolism (VTE) after unprovoked pulmonary embolism. Analyses were based on the double-blind randomised PADIS-PE trial, which included 371 patients with a first unprovoked pulmonary embolism initially treated during 6 months who were randomised to receive an additional 18 months of warfarin or placebo and followed up for 2 years after study treatment discontinuation. All patients had ventilation/perfusion lung scan at inclusion ( i.e. at 6 months of anticoagulation). During a median follow-up of 41 months, recurrent VTE occurred in 67 out of 371 patients (6.8 events per 100 person-years). In main multivariate analysis, the hazard ratio for recurrence was 3.65 (95% CI 1.33–9.99) for age 50–65 years, 4.70 (95% CI 1.78–12.40) for age >65 years, 2.06 (95% CI 1.14–3.72) for patients with pulmonary vascular obstruction index (PVOI) ≥5% at 6 months and 2.38 (95% CI 1.15–4.89) for patients with antiphospholipid antibodies. When considering that PVOI at 6 months would not be available in practice, PVOI ≥40% at pulmonary embolism diagnosis (present in 40% of patients) was also associated with a 2-fold increased risk of recurrence. After a first unprovoked pulmonary embolism, age, PVOI at pulmonary embolism diagnosis or after 6 months of anticoagulation and antiphospholipid antibodies were found to be independent predictors for recurrence. Residual pulmonary embolism is an independent predictor for recurrence after unprovoked pulmonary embolism http://ow.ly/jf0X30fQQGf